Perancangan Desain Media Promosi Visual terhadap Brand Mamaju Semarang - Zaki Dony Kezia Firmansyah; Rahina Nugrahani; Yon Ade Lose Hermanto (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasing competitiveness of the culinary industry requires businesses to adopt effective visual communication strategies capable of establishing a strong and memorable brand identity. However, Mamaju Semarang continues to face challenges due to the limited effectiveness of its existing promotional media in enhancing brand awareness. This study aims to address these challenges through the development of more strategic and communicative promotional media. The research employs the Design Thinking method, consisting of the empathize, define, ideate, prototype, and test stages, while adopting a Design-Based Research (DBR) approach to guide the problem analysis and design process. The resulting promotional media emphasize the visual appeal of the menu as the primary design element and include conventional leaflets, interactive leaflets, and supporting media such as tote bags. The design focuses on creating strong visual communication, maintaining a consistent brand identity, and incorporating interactive media to deliver a more engaging, memorable, and user-centered experience. Beyond serving as informational materials, these promotional media also function as visual communication tools capable of extending promotional reach through indirect engagement. Overall, the proposed design demonstrates significant potential to support promotional activities and strengthen brand awareness through sustained implementation.